Quarry Waste: Chances of a Possible Economic and Environmental Valorisation of the Montorfano and Baveno Granite Disposal Sites. (9th February 2012) - Dino, G. A.; Fornaro, M.; Trentin, A.
Abstract : The Montorfano and Baveno granite ore bodies are located in the Lake District (VCO-NE Piedmont). They were and are still quarried as dimension stones, with a consequent production of a huge volume of "waste." In 1995, an Italian company (GMM S.p.A) decided to invest in the valorisation of granite quarry waste as a secondary raw material. An in situ geological prospecting was carried out in order to evaluate the characteristics of the material and the thickness and volume of the useful disposal sites that could be used (by means of geophysical surveys). As a consequence of the field work, the amount of quarry waste was estimated as nearly 2 Mm 3 . Chemical analysis was carried out on 75 granite samples, in order to individuate the Fe2 O3 grade: from 1.321–2.593% of the original waste to 0.160–0.228% after the "dry process" treatment. Three different detailed maps that show the typology, the locations, and the quality distribution of the material in the dumping areas have been drawn up.